(untitled) (Scientia Agropecuaria, 2019)
The cocoa bean and its by-products are widely consumed in the world, due to their mineral content, functional compounds and antioxidant capacity, which vary according to how its processed. Fresh dried cocoa beans (FDB), dry fermented beans (FB) and cocoa paste (CP) were investigated, 31 samples in each case. Phosphorus, sodium, calcium, magnesium, copper, iron, zinc, manganese, cadmium lead, total polyphenols, anthocyanins, antioxidant capacity (ABTS, DPPH) expressed in Trolox equivalents (TE) were determined. Principal component analysis (PCA) was used. The mineral analysis established that 12 samples influenced CP1 and CP2. There was more calcium in the M26 sample of FDB, with 3.14%; potassium in the FDB, in M13, with 2.44%. Zinc in the FDB, was found in greater quantity in M30, M22, M23 and M9; with 90.46 ± 0.19 ppm in M30. Twenty-five samples reached values ≤ 0.61 ± 0.01 ppm of cadmium. There was a higher lead content in the FDB, in the M20 sample with 3.44 ± 0.05 ppm. The M10 sample, from FDB, presented the highest antioxidant capacity, with values of 591.50 ± 3.76 (ABTS) and 513.68 ± 0.84 (DPPH) μM TE/g.